How to get international construction projects delivered on time: from Chinese contractors’ perspective - Sun, Hongxin; Tang, Wenzhe; Duffield, Colin F.; Zhang, Lihai; Hui, Felix Kin Peng (Journal of Civil Engineering and Management, 2022)
67.9% of Chinese international construction projects are seriously delayed, which creates the potential for instability in its rapidly growing share of global contracting markets. A greater understanding of the reasons behind the challenges confronting international contractors is urgently required such that improvements can be developed that ultimately will benefit many countries. This study aims to investigate the time performance of international projects in developing countries and to explore the root causes of time overrun. Based on both quantitative and qualitative analysis of 112 case study projects, collected from 12 of the largest Chinse state-owned enterprises (SOEs), this study identifies the distinctive characteristics of three types of projects (late, acceptable, early) classified based on their time performances. It is established that time performance is significantly related to the contractor’s adaptability and project complexity. The results reveal the root causes of construction delays in international project delivery, which provides a structured and in-depth understanding of both internal and external time performance influential factors. The above findings provide sound basis for guiding practitioners in choosing appropriate strategies to improve project time performance, such as encouraging cross-cultural dialogues, integrating global resources and establishing long-term global partnerships with stakeholders.